Interactive children learning in object recognition via multimedia approach / Noridah Othman - Othman, Noridah (2004)
Multimedia software present the latest advances by providing an environment in which the traditional language teaching media of text, picture, graphics, task, sound and video can amalgamated. Market researcher tracking software tends have identified that the largest software growth recently has been in new tides and companies serving the early childhood educational market Of the people who own home computers and have young children, 70% have purchased educational software for their children to use (SPA Consumer Market Report 1996). The purpose of this thesis is develop a prototype model for children aged between 7-12 old years by provide an interactive learning environment through combination various of multimedia element in order to meet children's interest and needs and lead toward helping every children maximize flieir learning potential through 3D animation picture.